Wheat Grain Yield Response to Seed Cleaning and Seed Treatment as Affected by Seeding Rate During the 2019–2020 Growing Season in Kansas - R. P. Lollato; B. R. Jaenisch; L. Haag (Kansas Agricultural Experiment Station Research Reports, 2021)
The objective of this project was to evaluate winter wheat stand count and grain yield responses to seeding rate and its interaction with seed cleaning and seed treatment in Kansas during the 2019–2020 growing season. Experiments evaluating the response of the wheat variety ‘SY Monument’ to three seeding rates (600,000, 900,000, and 1,200,000 seeds per acre), three seed cleaning intensities (none, air screen, and gravity table), and two seed treatments (none, and insecticide + fungicide) were established in a split-split plot design conducted in a complete factorial experiment in ten Kansas locations. In-season measurements included stand count and grain yield. Despite a few location-specific results, the general trends were uniform enough to be generalized across locations. The average plant population across treatments ranged from 285,000 to 620,000 plants per acre, with the low populations occurring either in sites where severe freeze damage caused winterkill or in sites where sowing was followed by extremely dry periods. Grain yield across treatments ranged from 25 to 75 bushels per acre. Across locations, both stand count and grain yield increased with increases in seeding rate, with improvements in seed cleaning, and with the presence of a fungicide plus insecticide seed treatment across locations. This research is an initial step in evaluating the value of the seed certification process and does not compare certified seed versus bin-run seed. The seed used in this was study derived from commercial seed production fields (i.e., high quality seed) and not from commercial grain production fields, which are usually the case for bin-run seed.
Keywords: wheat; seed cleaning; seed treatment; seeding rate